MENINGKATKAN KINERJA PERUSAHAAN DENGAN MENERAPKAN KONSEP MANAJEMEN SUMBER DAYA MANUSIA STRATEGIK DALAM MENYONGSONG PERSAINGAN GLOBAL - Kadar Nurjaman; Ajam Mustajam; Syaifuddin Syaifuddin; Yusniar Lubis; Yusuf Abadi; Fauzan Rino (Komitmen: Jurnal Ilmiah Manajemen, 2020)
The concept of Strategic Human Resource Management has been a very important topic since the late 1980s. A company, if it wants to succeed in the competition in this global era, must be able to make human resource management plans that are capable and responsive to changes in world business in the future (strategic). This research aims to explain the concept of strategic human resource management (MSDMS) in an effort to contribute to company performance. MSDS research using a qualitative approach by using a literature review in presenting theories about research problems that are currently being carried out. There are two things that are analyzed in the concept of strategic human resource management (MSDMS). First, the relationship between HR strategy, HR practice and organizational performance is reviewed. As a result, the best practice approach has been used and yields useful results comparatively to the contingency approach and the configurational approach. Second, intervening factors and the causal relationship between HRM practice and organizational performance are analyzed. Retention results and multiple factors are found and placing too much control on causal relationships is unrealistic in empirical studies.